Analisis Bioetika Mengenai Eksploitasi Sturgeon (Acipenser sturio) dalam Industri Caviar dan Dampaknya terhadap Kelestarian Spesies - Rahajeng Galuh Tribuana; Sani Shofi Muthmainah; Vutri Suci Fatimah; Tri Cahyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Intensive exploitation of fish for caviar production currently threatens the extinction of sturgeon, one of the ancient fish species. Sturgeon egg harvesting is often carried out in inhumane ways, such as dissecting and killing parent fish, causing the natural sturgeon population to decline. The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) regulates the international trade of sturgeon and caviar, but weak law enforcement, high market demand, and widespread illegal trade all exacerbate the conservation status of this species. Conversely, caviar aquaculture, often considered an alternative, raises new bioethical issues, including long-term stress on fish, disease spread, decline in animal health, and the risk of hybridization that could threaten the genetic integrity of sturgeon populations. From a bioethical and environmental ethics perspective, it is difficult to justify the consumption of caviar as a luxury commodity at the expense of ecosystem sustainability and animal welfare. Therefore, sturgeon conservation requires a comprehensive approach that includes reducing consumer demand, improving legislation and enforcement, and preserving and restoring sturgeon's natural habitats.